Efficacy Assessment of Ultrasound Guided Lauromacrogol Injection for Ablation of Benign Cystic and Predominantly Cystic Thyroid Nodules - Dong, Yijie; Zhou, Jianqiao; Liu, Zhenhua; Luo, Ting; Zhan, Weiwei (Frontiers in Pharmacology, 2019)
Background To assess the efficacy and safeness of ultrasound guided lauromacrogol injection for ablation of benign cystic and predominantly cystic thyroid nodules. Methods From July 2016 to July 2018, 102 patients with 107 nodules were treated with ultrasound guided lauromacrogol injections for ablation and 43 nodules completed at least 12 months follow-up. Nodules sonographic characteristics, volume changes before and after USG-LIA, and complications were evaluated. Results Mean nodule volume decreased from 17.27 ± 20.51 ml to 5.35 ± 14.68ml (P < 0.05), and the overall resolution rate (volume reduction rate > 50%) was 91.67% in purely cysts and 75.90% in predominantly cystic nodules at the last follow-up. Within 6 months after treatment, the volume of the target nodule at each follow-up was smaller than the previous one (P < 0.001 for all). However, there was no significant difference of volume change between the 6th month and the 12th month. No severe complications occurred in this study. Conclusion Ultrasound guided lauromacrogol injection for ablation is an effective and safe treatment modality in both purely cystic and predominantly cystic thyroid nodules.